A Study of The Relationship Between Students' Belief and Attitude Toward Physics and GPA - Diyana, Tsania Nur; Pebriana, Irvany Nurita (International Journal of Education and Teaching Zone, 2022)
The Grade Point Average (GPA) score is the average value of each student who has studied for several semesters. This value is considered a representation of students' success in learning. Meanwhile, it is known that success in studying physics is not only influenced by cognitive abilities but also related to other things including students' beliefs and attitudes toward physics. This study aims to examine the relationship between students' beliefs and attitudes towards physics on GPA scores. This study used a survey research design with a total of 69 students from the third-year physics education department as subjects. Spearman's Rank Correlation analysis was used to determine the relationship between students' beliefs and attitudes toward physics with GPA scores. The results of the study show that there is a relationship between the two but with a very weak relationship. The correlation coefficient value obtained is 0.132 while the significance value is 0.281. These results indicate that the relationship that occurs between the two variables is not significant.